The post-larval metabolism rate of vannamei shrimp (Litopenaeus vannamei) in terms of oxygen consumption and ammonia excretion at different salinities - Burhanuddin, Burhanuddin; Malik, Abdul; Haris, Abdul; Anwar, Asni; Ayuzar, Eva (Acta Aquatica: Aquatic Sciences Journal, 2024)
The development of vannamei shrimp (Litopenaeus vannamei) cultivation still faces many problems. One of them is the availability of seeds whose growth is slow and variable, as well as high mortality after being stocked in ponds. This study aimed to examine the post-larval metabolic rate of tiger prawns in terms of oxygen consumption and ammonia excretion at different salinities. The research was carried out November - December 2023 in the Takalar Intensive Pond Unit, after which vannamei shrimp larvae with a density of 100 individuals/l were reared for acclimation for two weeks in tanks containing media water with a salinity of 10, 20 and 30 ppt. At the end of the acclimation period for the test shrimp, a respirometer was prepared to measure oxygen consumption and ammonia excretion. The results of the research showed that the average value of oxygen consumption after vannamei shrimp larvae occurred at a salinity of 10 ppt, then followed respectively at a salinity of 30 and 20 ppt. The results of the analysis of variance showed that salinity had a very significant effect (P<0.01) on oxygen consumption after vannamei shrimp larvae, but in the LSD follow-up test it appeared that only the 10 ppt treatment was very significantly different (P<0.01) and the same results occurred. on ammonia excretion, although the test of variance (LSD) had no significant effect. The survival rate and post-larval growth of vanamei shrimp reached the highest average value at a salinity of 20 ppt with very significantly different variance results. Based on the measurement results above, the optimum metabolic rate after vannamei shrimp larvae occurs at a salinity of 20 ppt (isotonic conditions occur between the shrimp's body fluids and the medium).Keywords: Ammonia Excretion; Metabolism Rate, Oxygen Consumption; Vanname Shrimp